Rethinking the 10‐pack‐year rule for favorable human papillomavirus–associated oropharynx carcinoma: A multi‐institution analysis. Issue 12 (13th March 2020) - Broughman, James R.; Xiong, David D.; Moeller, Benjamin J.; Contrera, Kevin J.; Prendes, Brandon L.; Lamarre, Eric D.; Ku, Jamie A.; Burkey, Brian B.; Woody, Neil M.; Joshi, Nikhil P.; Adelstein, David J.; Geiger, Jessica L.; et al.
Abstract : Background: De‐intensified treatment strategies for early human papillomavirus–positive (HPV+) oropharynx cancer (OPC) rely on selecting patients with an excellent prognosis. The criterion for enrollment in current de‐intensification trials is ≤10 pack‐years. More nuance to the pack‐year criteria may expand enrollment, improve patient outcomes, and prevent overtreatment. It was hypothesized that patients with more than 10 pack‐years may experience favorable outcomes if smoking cessation has been achieved. Methods: From an institutional review board–approved database, patients with HPV+ oropharyngeal squamous carcinoma treated definitively with radiation with or without chemotherapy were retrospectively identified. Patients with a history of smoking who were eligible for national de‐intensification trials were included (cT1‐2N1‐2b or T3N0‐2b [American Joint Committee on Cancer, seventh edition]). Cox regression with penalized smoothing splines was used to evaluate nonlinear effects of cessation. Recursive partitioning analysis (RPA) was used to objectively search for relationships between the 2 colinear variables (pack‐years and time since cessation). Results: Among 330 patients meeting the inclusion criteria, 130 (40%) were never smokers,  139 (42%) were former smokers, and 61 (18%) were current smokers. With standard therapy, all former smokers achieved a progression‐free survival (PFS) rate higher than 91%, regardless of pack‐year exposure. Nonlinear Cox regression demonstrated that more recent cessation was associated with significantly worse PFS even among those with ≤20 pack‐years. RPA demonstrated that only current smokers experienced a 2‐year PFS rate lower than 91%; former smokers, regardless of pack‐years, experienced a 2‐year PFS rate higher than 91%. Conclusions: The 10‐pack‐year rule may not apply to all early HPV+ OPCs, particularly for former smokers. Future randomized de‐intensification trials should consider a broader and more nuanced approach until the predictive role of smoking status is established. Abstract : This analysis demonstrates that the 10‐pack‐year rule may not apply to all early human papillomavirus–positive oropharynx cancers, particularly for former smokers.